The Influence of Brand Image and Product Design on Purchase Decisions for Brodo Brand Shoes on the E-Commerce Shopee (Case Study: Students of the 2021-2025 Regular Morning Class of the Faculty of Economics, National University of Pasim) - RAMDHANI, Dahlan; DANILIA, Friska (PT. Keberlanjutan Strategis Indonesia, 2025)
Purpose:This research was conducted on students of Universitas Nasional Pasim Faculty of Economics Regular Morning Class of 2021. The purpose of this study was to determine how brand image and product design influence the purchasing decision of Brodo brand shoes in an e-commerce shop (Case Study of Students of Universitas Nasional Pasim Faculty of Economics Regular Morning Class of 2021).Methodology:The research method used in this study is descriptive and associative. The unit of analysis is the individual, namely the 2021 Regular Morning Students of the Faculty of Economics, National University of Pasim. The sample size was 95. The sampling technique used in this study was based on certain characteristics. The analytical method used was multiple linear regression analysis, and the validity and reliability of the research instrument were also tested.Findings:Based on the research results it shows that there is a partial and simultaneous influence of brand image and product design variables on purchasing decision variables.Implication:The influence of brand image on purchasing decisions is 33.9%, while product design on purchasing decisions is 48.9%. The influence of brand image and product design on purchasing decisions is 82.8%.